THE EFFECT OF ETHANOLIC EXTRACT OF CENTELLA ASIATICA (L) URBAN ADMINISTRATION TOWARDS THE THICKNESS OF PYRAMIDAL LAYER IN THE CA1 REGION OF HIPPOCAMPUS OF SPRAGUE DAWLEY RATS AFTER CHRONIC RESTRAIN STRESS - Anggraeni Janar Wulan; Brian Wasita; Nanang Wiyono (JUKE Unila, 2014)
Background: Stress has been shown can change the structure of the brain, especially in the cornu ammonic (CA) I region of hippocampus. Centella asiatica or pegagan as herbal neuroprotector was investigated. The study aimed to determine the effect of ethanolic extract of C. asiatica to the thickness of pyramidal layer in the CA1 region in rats subjected to chronic restrain stress (CRS). Method: This experimental study used post test only group design. Thirty five rats were divided into 6 groups: non stress group (control) and stress only group pulvis gum arabicum (PGA), positive control group (treated with fluoxetin 10mg/kgBW), and 3 treatment groups are treated with C. asiatica 150, 300, and 600mg/kgBW respectively. All groups except non stress group were subjected to CRS, for 6 hours per day for 21 days. Fluoxetin, PGA, and C. Asiatica were applied 30 minutes before CRS done. Rats were sacrificed at the end of 24th day and were perfused transcardially. Processed brain tissue stained with toluidine blue, and measured with Image Raster program. Result: The thickness of pyramidal layer in the CA1 region are increasing significantly in treatment groups which treated with 150 and 300 kg/BW of C. asiatica, but not significant which treated with 600mg/kgBW ethanolic extract of C. asiatica. Conclusion: Ethanolic extract of C. asiatica can improve thickness of pyramidal layer in the CA1 region of hippocampus of Sprague Dawley rats after chronic restrain stress. [JuKe Unila 2014; 4(8):202-207]